Access audit in religious buildings and public spaces in old Damascus city in Syria - Zen, Ismawi; Abdul Rahim, Asiah; Abu Bakar, Aniza; Abdullah, Fadzidah (IIUM Press, IIUM, 2012)
Certain numbers of issues regarding lack of facilities in providing the user friendly environment for the people with disabilities (PWDs) has been raised by various societies of the disabled as they a/so need access to these public spaces such as the religious building, public toilets and other public spaces especially in heritage areas including recreational areas. Outdoor environment is as important as the internal environment that should be considered the typical needs of a various users. Elements of the outdoor environment are such as landscape, hardscape, street furniture, public facilities, gardens, open spaces and courtyards. Therefore, it is important to have accessible built environments to the aged and persons with disabilities to enable them to move independently without any assistance and make them feel they are part of the society. The research aim is to determine the need of the PWDs and the aged, for their outdoor living environment as well as the suitable facilities to be provided for them in public spaces of the Old Damascus, Syria. it is hoped that the access audit done in Old Damascus, Syria will benefited in generating more ideas of improving the current condition of heritage areas, which can be relevant to the public realms in Malaysia and other parts of the Muslim world.